Pengaruh Promosi, Produk, Harga Dan Tempat Dalam Menarik Minat Pembeli Pada Hypermart Kota Bengkulu - Inka Parolita; Ida Anggriani; Nirta Vera Yustanti (Penerbit Jurnal Indonesia, 2023)
At this time Indonesia is facing a period of globalization and the development of information technology is accelerating. Indonesia must prepare itself and be able to plunge in the era of globalization, one sector that must be considered is the retail business sector, where retail businesses are experiencing quite rapid development in recent years. Producers who produce goods and services not only pay attention to the goods and services they produce, but must be able to pay attention to how the goods and services they produce are known to consumers and reach the hands of consumers in accordance with consumer desires and expectations. The purpose of this study was to determine the effect of promotion, product, price and place in attracting buyers at Hypermart Bengkulu City. The sample used in this study amounted to 84 people who had shopped at Hypermart. The sampling technique uses the Slovin formula by taking a 10% confidence level. Data is processed in the form of numeric data (numbers) using a Likert scale. The data collection method in this study is in the form of a questionnaire. The data is processed using spss for windows version 25. The analysis method uses quantitative methods, namely by using multiple linear regression analysis. The results of the study show that there is a significant influence between promotion on consumer buying interest in Hypermart Bengkulu City, which means that the more promotion is held, the more consumer buying interest will increase. There is a significant influence between products on buying interest at Hypermart Bengkulu, which means that the better the quality of the products offered, the more consumer buying interest will increase. There is a significant effect on price on buying interest in Hypermart Bengkulu, which means that the more affordable the price offered, the more consumer buying interest will increase. There is a significant effect on place on buying interest in Hypermart Bengkulu City, which means that the more strategic the place that is reached, the more consumer buying interest in Hypermart Bengkulu City will increase.